Pengaruh Penambahan Eco-Enzyme dalam Air Minum terhadap Performa Produksi pada Ayam Kampung Ipb-D1 - Pit Ay, Venansius Ronaldo H.; Konda Malik, Agus; Theedens, J. F. (Animal Agricultura, 2024)
This research aims to examine the effect of adding eco-enzymes to drinking water on the production performance of IPB-D1 native chickens. The research was carried out for 9 weeks in Noelbaki Village, Central Kupang District, Kupang Regency. This research used 72 IPB-D1 village chickens. The design used was a completely randomized design consisting of 4 treatments and 6 replications. The treatments tried were differentiated based on the level of use of eco-enzyme in drinking water, namely: P1 = feed + drinking water without eco-enzyme (control), P2 = feed + eco-enzyme 1 cc/liter of water, P3 = feed +eco-enzyme 2 cc/liter of water, P4 =feed+ eco-enzyme 3 cc/liter of water. The variables measured were the body weight of the chicken at the start of laying eggs, the weight of the eggs at the start of laying eggs and the age of the chicken at the start of laying eggs. The results of the analysis of variance showed that the treatment had no significant effect (P>0.05) on the body weight of the chicken at the start of laying eggs, the weight of the eggs at the start of laying eggs and the age at which chickens started laying eggs. Based on the results of this research, it can be concluded that the addition of eco-enzyme to drinking water has the same effect on the body weight of chickens at the start of laying eggs, the weight of eggs at the start of laying eggs and the age at which chickens start laying eggs in IPB-D1 chickens.